2010
DOI: 10.1016/j.micres.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation as a strategy for cleaning up of soils contaminated with aromatic compounds

Abstract: The contamination of soil with aromatic compounds is of particular environmental concern as they exhibit carcinogenic and mutagenic properties. One of the methods of their removal from soil is bioaugmentation, defined as a technique for improvement of the degradative capacity of contaminated areas by introduction of specific competent strains or consortia of microorganisms. The efficiency of bioaugmentation is determined by many abiotic and biotic factors discussed in this paper. The first include chemical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
179
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(202 citation statements)
references
References 84 publications
2
179
0
9
Order By: Relevance
“…Despite non-addition of inoculum to Treatment D, it still indicated that 16.5% of Zn reduction. This might be due to the presence of pre-existing microbes in the leachate-induced soil, and such microbes may have the capacity to reduce or transform portion of heavy metals [8] without prior amendment. Similarly, Treatment A recorded up to 25% reduction, which may be influenced by pH distribution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite non-addition of inoculum to Treatment D, it still indicated that 16.5% of Zn reduction. This might be due to the presence of pre-existing microbes in the leachate-induced soil, and such microbes may have the capacity to reduce or transform portion of heavy metals [8] without prior amendment. Similarly, Treatment A recorded up to 25% reduction, which may be influenced by pH distribution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After 14 days of chromium exposure, the amount of Bacillus subtilis in 15% bacteria addition reactor increased by the time of test period. This case happened because Bacillus subtilis had already adapted and were able to live well enough [15]. The increasing of Bacillus subtilis colonies number occurred at B50 reactor which is had the lowest chromium concentration.…”
Section: Number Of Bacterial Colonymentioning
confidence: 98%
“…effects (Mrozik and Piotrowska-Seget, 2009;Mishra et al, 2010). Because heavy metal and antibiotic resistance genes are often found on the same mobile genetic element, metal pollution often promotes the emergence of antibiotic resistances in exposed organisms, which fact has also a growing concern in natural and clinical settings (Knapp et al, 2011).…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 194-211mentioning
confidence: 99%